Oral Inflammation and Bacteremia: Implications for Chronic and Acute Systemic Diseases Involving Major Organs - Hirschfeld, Josefine; Kawai, Toshihisa (Cardiovascular & Haematological Disorders - Drug Targets, 2015)
Gingivitis and periodontitis are both highly prevalent gum diseases characterized by an accumulation of a polymicrobial biofilm (dental plaque) around teeth and inflammation in adjacent soft tissues. During dental procedures, even tooth brushing, these bacteria and their components, such as endotoxin, can easily disseminate into the systemic circulation through minor or major gingival injuries. Particularly in immuno-compromised subjects or patients with preexisting pathologic conditions, bacteremia may lead to bacterial infection of distant organs, which may cause immunological reactions. Oral bacteria and endotoxins have been found in sepsis, infective endocarditis, lung infection, liver disease and many other potentially lethal disorders. This article presents a review of the possible pathologic consequences of bacteremia originating in the oral cavity and points out the most commonly affected organs as well as preventive and treatment measures. At the present time, plaque control by subjects and/or dental professionals is one of the most effective means to prevent the onset and progression of oral bacteremia-induced systemic diseases.
Keywords: periodontitis